2012
DOI: 10.5713/ajas.2011.11425
|View full text |Cite
|
Sign up to set email alerts
|

Forsythia suspensa Extract Has the Potential to Substitute Antibiotic in Broiler Chicken

Abstract: Two experiments were conducted to investigate the potential for Forsythia suspensa extract (FSE) to substitute for antibiotic in broiler chicken. First, a well-diffusion assay procedure and a 2-fold dilution method were used to determine the bacteriostatic activity of FSE on Escherichia coli K88, staphylococcus aureus, and salmonella was assayed. An inhibitory effect of FSE was observed on the growth of these bacteria. This effect seems to be dose depended, which disappeared after 25.00, 12.50, 1.56 mg/ml. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…Decreased number of pathogenic bacteria in the gut may improve proliferation of epithelial cells to build villus in the gut and thus enhance intestinal morphology (Mourāo et al 2005). Antioxidants may fix the intestine impairment caused by oxidative stress and improve intestinal morphology in weaned pigs (Han et al 2012). In this study, the change of microflora composition in the colon and rectum and increased serum total antioxidant capacity may partly explain the enhanced intestinal morphology.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Decreased number of pathogenic bacteria in the gut may improve proliferation of epithelial cells to build villus in the gut and thus enhance intestinal morphology (Mourāo et al 2005). Antioxidants may fix the intestine impairment caused by oxidative stress and improve intestinal morphology in weaned pigs (Han et al 2012). In this study, the change of microflora composition in the colon and rectum and increased serum total antioxidant capacity may partly explain the enhanced intestinal morphology.…”
Section: Discussionmentioning
confidence: 70%
“…Antioxidants may fix the intestine impairment caused by oxidative stress and improve intestinal morphology in weaned pigs (Han et al . ). In this study, the change of microflora composition in the colon and rectum and increased serum total antioxidant capacity may partly explain the enhanced intestinal morphology.…”
Section: Discussionmentioning
confidence: 97%
“…A number of these markers in pigs fed FSE or COS either alone or in combination were lower than the CON group. Previous studies showed that FSE improved intestinal morphology and increased intestinal healthy microbiota in broilers (Han et al ; Zhang et al ) while COS reduced intestinal permeability in weaned piglets (Yang et al ). Our results were consistent with previous studies, and indicate FSE or COS could alleviate intestinal injury.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, to assess the effect of dietary treatment on feed utilization, total tract apparent nutrient digestibility was determined. It was reported that FSE and COS could promote gut health of pigs by modifying small‐intestinal mucosal architecture and modulating intestinal microbial ecosystem (Han et al ; Liu et al , ; Zhang et al ). In our study, dietary supplementation with COS, FSE or a combination of both increased dry matter and energy digestibility on days 14 and 28, which indicated a benefit to the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation